The effects of the unexpected cautionary and annual earnings announcements on the Price Formation Process: evidence from the JSE - Stephans, Mandla-Kayise (Department of Finance and Tax, 2021)
Certainly, a decision to (dis) invest (buy/sell) in securities is largely influenced by future expectations to which in turn is informed by the fundamental analysis of historical prices. The investor supposedly extrapolated on the historical prices if below the mean you buy and vice versa. The average security prices must be the product of the passing of time but most importantly the direction must be susceptible to a particular point in time. Investor decision-making involves a selection of a combination of the individual security characteristic with the market sentiment (bearish or bullish). The market sentiments are measured on time passed, i.e., market prices are either higher or lower relative to historical prices and the investor holding period wish. Valuation is nothing but a timing exercise to which the future perspective is forged on the future outlook of both micro and macro-economic factors. The valuation is relative to a true return generating process for a ‘true' single security market portfolio, i.e., expected future earnings. The occurrence of ‘unexpected earnings' creates an expectation of above ‘true' market portfolio returns, i.e., abnormal returns (ARs). This study is premised on the appreciation and understanding of the manifestation of a ‘true' single stock market portfolio. The study presents the analysis of the contemporaneous association of unexpected earnings also referred to as cautionary earning or ‘earnings surprise' published in the Trading Statement releases (hereinafter referred to as ‘releases') and security price movement. This research study is the second to investigate, at least to the researcher's knowledge after Cata (2015), the entire price formation process on the effects of unexpected cautionary and annual earnings announcements on security market prices of the JSE listed. Firstly, the expectations are that security prices adjust immediately to earnings and /or price-sensitive market information when made public. Secondly, since earnings information is fully impounded onto security prices a not statistically significant ARs are earned on and around the disclosures. Lastly, no statistically significant cumulative abnormal returns (ie CARs) post-earnings releases and announcements (I.e., PEADs) and any non-random security return drift indicate a level of inefficiency. The study adopted a return based unexpected earnings measures or model of Foster, Olsen and Shevlin (1984), and Van Rensburg's (2002) two-factor Arbitrage Pricing Theory (APT) to be a factor analytic procedure for assessment of a true return generating process for a ‘true' single stock market portfolio. The empirical evidence suggests investors revise the security valuations to an extent of 85 to 90 (Ball and Brown, 1968) and 85 to 98 (Kornik, 2005) percentage before an unexpected earnings announcement. This observation strengthens the argument that other timelier sources of information are already factored into share price prior to unexpected earnings releases. An alternative argument on legitimate information dissemination and other timelier sources of information provides a compelling argument for an all-encompassing multi factor-model in the context of JSE. According to Dr. Holman (2018) a measured or weighed multi factor-model consisting of a metal index, interest rate (i.e., 5 or 10 years repo rate), inflation rate, currency, beta, economy (i.e., GDP growth), stock size (small vs large capitalisation), leverage, unemployment rate, values such as price to book value or price-earnings (P/E) ratios, momentum (market biases – a big thing). Perhaps this to provide an explanatory power or rationale of the full market reaction when all price-sensitive factors are considered at once and rated accordingly is to explain the extent of the usefulness of the market information from a piece of specific unexpected event news. In so doing provide for an opportunity to improve on the true return generating process for a ‘true' single stock market portfolio from Van Rensburg's (2002) two-factor Arbitrage Pricing Theory (APT). The study's results come from an observation of five unexpected earnings models or measures and the trading statement news sign and size to ascertain the size of the security price movement and return drift. The evidence gathered is conclusive concerning the association of the information content generated through unexpected earnings disclosures and the average CARs and their t-statistic test found to be significantly different from the theoretical or expected zero return. However, the outcome of t-statistic tests is not statistically significant at a 5% significance level of significance over the observation period, therefore, they cast doubt on the use of the initial response to consistently earn earnings above average normal returns. The study observed a security price movement in line with ‘good' and ‘bad' news portfolios on [-3; -1] and [-1; -1] releases and [-2; -1] announcements in support of Kornik's (2005) observation of a significant portion of the market reaction occurring in the two days prior to the announcement date. Kornik (2005) suggests that either a substantial information leakage or simply legitimate information dissemination and /or anticipation (ie from other timelier sources of information) allows for investors to correctly adjust their earnings prediction through company analysis and /or interviews with management prior to unexpected earnings announcements. This study conclusion is that there is evidence of significant association to suggests an investor reassessment of their beliefs/expectations on the occurrence and the size of ‘earnings surprise' and unexpected annual earnings. The finding violates the Efficient Markets Hypothesis (EMH) which assumes that security prices are instantly and fully reflective of all available information and that investors cannot use public information to consistently gain above-normal returns (Cata, 2014). It important to highlight that, contrary to Murie's (2014) and Cata's (2015), the study found no suggestion that investors wait to determine the uncertainty regarding the specific reason for the change in earnings on the releases date to be alleviated via the announcement or publication of actual earnings to conclude on inconsistencies observed with semi-strong form market efficiency. First and foremost a conclusion must be reached based on significant abnormal returns earned on the market news in periods surrounding earnings releases and announcements strengthened by the outcome of the unexpected earnings measures or models. Secondly, Murie (2014) correctly pointed out that unexpected earnings models or measures are not an information source to the market, unlike trading statement releases or earnings announcements. Thirdly, Murie (2014) did not investigate the entire price formation process and his [+3;+60] post-release would have included the effects of earnings announcements considering that on average it trails by approximately 9 trading days from the releases. What is known based on this study observation and Kornik's (2005) assertion is that new information should be impounded into the security price within a week (i.e., 5 days on average) of the announcement. The significant price movements appear to be taking place on intraday releases, previous studies show that the focus was only on closing and opening security prices. The observed price movement prior to, on the event date and after the release date supports the findings of Ball and Brown (1968) that the market uses other timelier sources of information available in the market to revise share valuations (Murie, 2014). However, the unexpected earnings are partly timely to the extent of approximately 15 to 10 (Ball and Brown, 1968) and /or 15 to 2 percent (Kornik, 2005) resulting from investors' revision of the security valuations to between 85 to 90 percent (Ball and Brown, 1968) and 85 to 98 (Kornik, 2005) percent before an unexpected earnings announcement. The researcher's view is that, since the expectations, in most cases, are influenced by the analysis of previous earnings announcements, the actual results and analysts' estimation, therefore, to a certain extent the price movement reflects the evolution of the investor/market sentiment and overtime change in earnings is judged in this context (i.e., reaction). At this point, it is advisable that future research looks into or considers subdividing the releases into voluntary (i.e., management forecast) and compulsory release (i.e regulatory requirement since 2010) as the latter appears to influence the extent of investors' response.